Linguistic features and legibility of the consolidated audit reports: An original investigation from the Tunisian case - Mondher Fakhfakh (Cogent Business & Management, 2016)
The consolidated audit report is a source of information that strengthens corporate governance and financial communication. The purpose of this paper is to analyze the linguistic features and readability of auditors' reports on consolidated financial statements in Tunisia. The literature was examined in order to obtain a rigorous approach that explores the content and structure of audit messages. The study sample consists of 42 consolidated audit reports that are related to several sectors. The empirical results show that these reports are not readable by all users of the consolidated financial statements. The same results confirm the significant impact of specific determinants on readability of audit reports such as modification of the opinion of the independent auditor and the audit report lag.
Keywords: 650